Beyond Compliance: The Role of Corporate Governance, Workplace Spirituality and Job Satisfaction in Enhancing Organizational Citizenship Among East Javanese Lecturers - Ria Mennita; Astuti, Widji; Assih, Prihat (The International Journal of Accounting and Business Society, 2024)
Purpose—This paper aims to investigate how good corporate governance (GCG) and workplace spirituality (WS) influence organizational citizenship behaviour (OCB) through job satisfaction (JS) among lecturers in East Java. The study explores how corporate governance practices, spiritual values and psychological aspects within the workplace contribute to voluntary behaviours beyond job descriptions. Design/methodology/approach — This paper employs a quantitative approach to examine the effects among variables and uses Structural Equation Modelling by AMOS 22 to analyze 200 East Java lecturers' responses. Data is collected through structured surveys. Findings — The results demonstrate a significant effect between good corporate governance, workplace spirituality, and job satisfaction on OCB among lecturers. The p-value result shows that the significance level of GCG is 0.011, WS is 0.007, and JS is 0.000; each p-value is smaller than 0.05, meaning all exogen variables impact OCB. This result also validated the mediation effect of job satisfaction. The result of the direct impact of GCG is 0.209., and WS is 0.256. While the total influence shows that the value of GCG is 0.487 and WS is 0-543. Based on the results of the total effect, which is greater than the direct effect, there is a mediation effect of JS. The findings indicate that lecturers who perceive their work environment as ethical and supportive of their values are likelier to engage in behaviours beneficial to the organization. Practical implications—The findings underscore the importance of organizations implementing corporate governance and workplace spirituality practices to foster job satisfaction and OCB effectively. University leaders should consider aligning GCG policies with spiritual values to create a supportive and ethical work environment. Neglecting either aspect may lead to an imbalance, reducing the likelihood of positive, citizenship-oriented behaviour among lecturers. Originality/value—This paper contributes a combination indicator of workplace spirituality and examines the limited research on governance, spirituality and organizational behaviour. It also provides insights into how an integrated approach can enhance workplace behaviours, which may be particularly valuable for organizations in regions where spiritual and ethical values play a significant role in professional life. Paper type — Quantitative Study